Controlled sulfurization of MnCO3 microcubes architectured MnS2 nanoparticles with 1.7 fold capacitance increment for high energy density supercapacitor. (1st April 2019) - Pujari, R.B.; Lokhande, V.C.; Patil, U.M.; Lee, D.W.; Lokhande, C.D.
Abstract: Recently, sulfurization and phosphorylation protocols are employed in porous nano-materials preparation beneficial to improve energy density and power density of pseudocapacitors. Due to well-defined redox activity and higher theoretical capacitance, manganese sulfide electrode is used in supercapacitor application. In present work, MnCO3 microcubes are converted into MnS2 nanoparticles using cost-effective high diffusion rate sulfurization method. Reducing size of material from microcubes to nanoparticles has facilitated rate capability in the material along with improved capacitance. MnS2 nanoparticles exhibit 713 Fg -1 specific capacitance at 5 mVs −1 scan rate compared with 407 Fg -1 obtained for MnCO3 microcubes. The impedance study analyzes improvement in interfacial conductivity for MnS2 nanoparticles observed form 1.83 Ωcm −2 equivalent series resistance in comparison with 2.35 cm −2 for MnCO3 microcubes. Fabricated solid state MnS2 //MoS2 asymmetric supercapacitor exhibits 41.7 Whkg −1 energy density, and 450 Wkg -1 power density with the respectable 88 % capacitance retention for the continuous 2000 CV cycles charging and discharging at 100 mVs −1 scan rate.